Effect of FLOT2 Gene Expression on Invasion and Metastasis of Colorectal Cancer and Its Molecular Mechanism under Nanotechnology and RNA Interference. (4th April 2022) - Zhong, Chonghan; Zheng, Fangfang; Ye, Shanping; Gao, Gengmei; He, Penghui; Liu, Dongning
Abstract : The study is aimed at investigating the effect of the FLOT2 gene on invasion and metastasis of colorectal cancer (CRC) cells and the corresponding molecular mechanism by preparing polylysine-silicon nanoparticles. Specifically, polylysine was used to modify the silica nanoparticles prepared by the emulsification method to obtain polylysine-silicon nanoparticles. The characterization of polylysine-silicon nanoparticles was completed by nanoparticle size analyzer, laser particle size potentiometer, and transmission microscope. The influence of polylysine-silicon nanoparticles on the survival rate of CRC cell line HT-29 was detected using the method of 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT). The FLOT2-siRNA expression vector was constructed and transfected with HT-29. The HT-29 transfected with empty plasmid was used as the negative control (NC). Western Blot (WB) and reverse transcription-polymerase chain reaction (RT-PCR) were used to detect expression levels of FLOT2 gene and epithelial-mesenchymal transition- (EMT-) related genes. Transwell invasion assay, Transwell migration assay, and CCK8 assay were used to detect the cell invasion, migration, and proliferation. The results showed that the average particle size of polylysine-silicon nanoparticles was 30 nm, the potential was 19.65 mV, the particle size was 65.8 nm, and the dispersion coefficient was 0.103. At the same concentration, the toxicity of silicon nanoparticles to HT-29 was significantly lower than that of liposome reagent, and the transfection efficiency was 60%, higher than that of liposome reagent (40%). The mRNA level and protein expression of the FLOT2 gene in the FLOT2-siRNA group were significantly lower than those in the NC group (P < 0.01 ). The optical density (OD) value of the NC group and the blank control (CK) group were significantly higher than that of FLOT2-siRNA cells (P < 0.01 ). The OD value of FLOT2-siRNA cells was lower than that of NC cells at 48 h, 72 h, and 96 h (P < 0.01 ). The mRNA levels and protein expressions of MMP2 and vimentin in the FLOT2-siRNA group were significantly lower than those in the NC group and CK group (P < 0.01 ). The mRNA level and protein expression of the E-cadherin gene in the FLOT2-siRNA group were significantly higher than those in the NC group and CK group (P < 0.01 ). In conclusion, an RNA interference plasmid with high transfection efficiency and low cytotoxicity was established based on nanotechnology. siRNA-mediated FLOT2 protein inhibits the invasion, migration, and proliferation of CRC cells by regulating the expression changes of EMT-related genes, which provides a scientific basis for clinical treatment of CRC.